PKPM Pelatihan Public Speaking dan Styles Dakwah Dalam Upaya Meningkatkan Kualitas Mubalighat Pimpinan Wilayah ‘Aisyiyah Sumatera Utara - Rasta Kurniawati Br.Pinem; Mavianti Mavianti; Rizka Harfiani (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2019)
The nature of communication is the process of delivering messages from the messenger (communicator) to the recipient of the message (communicant). So that the process requires a strategy so that the message can be easily received by the recipient of the message. Every human being must make communication, especially when in an organization. Along with the development of the quality age of the communicator, in this case all members of the Regional Leadership ‘Aisyiyah North Sumatra who are business cadres must be upgraded in their capabilities and quality. Especially in carrying out the mandate and vision and mission ‘Aisyiyah. So there is no longer a mindset that assumes that those who have the ability to preach especially before the public are only the duty of those who are in the Tabligh Assembly and the Da'wah Council only. Therefore the author wants to hold and provide training in public speaking & da'wah styles to all members of the Regional Leadership ‘Aisyiyah North Sumatra in order to realize the quality of each member of the Regional Leadership‘ Aisyiyah North Sumatra who realizes that his role as a cadre and mubalighat.Keywords: Public Speaking Training, Styles Dakwah, Mubalighat Quality